Antecedents of customer satisfaction in the Islamic bank of Thailand : a relationship marketing perspective - Sidi, Tarek (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
In Thailand, Islamic financial products and services are offered by the Islamic Bank of Thailand (IBT), some conventional banks and a number of Islamic financial cooperatives. Thus, this means that IBT is faced with a highly competitive marketplace. In a competitive milieu, it is crucial for the firm to focus on establishing and enhancing a stronger relationship and engagement with customers for long-term purposes. Therefore, the current study encourages IBT to perform relationship marketing (RM). Thus, this study aims to identify the antecedents of customer satisfaction in the context of IBT. The proposed dimensions of RM were extracted from RM literatures which comprised of trust, commitment, communication, bonding and empathy. The data was collected from 314 IBT customers in Songkhla and Pattani, Thailand, using structured questionnaire technique. Whereas 302 applicable questionnaires were used to perform multiple regression analysis to test the hypotheses. The findings show that trust, communication, bonding and empathy has significant positive effects on customer satisfaction among the customers of IBT. Empathy appears as the most important dimension in satisfying the customers followed by bonding, trust and communication. Interestingly, only commitment was found to have no significant association with customer satisfaction. The findings of this study provide theoretical and conceptual implications on RM and Islamic banking. Moreover, the findings provide a significant implication for managers, marketers of IBT and practitioners in the relevant fields. Hence, the findings of this study provide insight on implementation of RM in Islamic banks particularly in Thailand and other countries in order to satisfy customers.